Lieutaud’s triangle lesion and urodynamic disorders in bladder cancer according to magnetic resonance imaging data - E. G. Grigor'ev; I. G. Frolova; S. A. Velichko (Вестник рентгенологии и радиологии, 2016)
Objective: to estimate the capabilities of magnetic resonance imaging (MRI) in revealing bladder tumor in relation to its sizes and location and in diagnosing concomitant urodynamic disorders.Material and methods. A total of 93 patients (78 men and 15 women; mean age, 62.1±12.2 years) with bladder cancer were examined. еxaminations were made using 1.5 T MRI according to an extended protocol with a mandatory inclusion of diffusion weighted images; dynamic contrast-enhanced MRI was carried out in 86 patients.Results. There were single nodules in 48.7% of the patients and multiple bladder wall lesions in 51.3%. Bladder wall injury involving the  functional area of Lieutaud’s triangle was revealed in 67.5% of the patients. Single and multiple tumors in Lieutaud’ triangle were observed in 58.9 and 80.5% of cases. Ureteral orifice involvement led to secondary ureterectasia in 68.2%.Conclusion. As the number of tumors detected in the bladder increases, the risk of tumors in Lieutaud’s triangle injury rises. The involvement of the triangle into the pathological process is accompanied by impaired urodynamics as ureterectasia in every four cases (26.8%; p < 0.008). It is shown that dynamic contrast-enhanced MRI must necessarily be  performed to better visualize a tumor and to determine its relationships to the underlying wall and basic structures of the bladder.